PO34 | A negative oncologic follow up doesn’t always really mean no cancer: two case report of cancer-associated thrombotic microangiopathy (Bleeding, Thrombosis and Vascular Biology)
Background: Cancer-associated thrombotic microangiopathy (CA-TMA) is a rare but severe complication of malignancy characterized by microangiopathic hemolytic anemia (MAHA), thrombocytopenia, and organ dysfunction, typically in the absence of thrombotic thrombocytopenic purpura (TTP)-defining ADAMTS13 deficiency. Its pathophysiology is poorly understood, but it is hypothesized to involve direct endothelial injury by tumor cells, cytokine-mediated microvascular damage, or tumor-related procoagulant activity. Most cases of CA-TMA have been reported in patients with mucin-producing adenocarcinoma (e.g. gastric, breast cancer) and in those with disseminated malignancies, but also described in cases with isolated invasion of the bone marrow. Treatment primarily focuses on controlling the underlying malignancy; plasma exchange (PEX) and steroids, commonly used in TTP, are generally ineffective in CA-TMA. Prognosis remains poor, often due to advanced-stage malignancy and limited responsiveness to oncologic treatment. Prompt recognition and accurate diagnosis, including consideration of bone marrow biopsy (BMB), are critical for optimal management.